Preparation method and application of copper-manganese composite monolithic metal substrate catalyst

By preparing copper-manganese composite metal substrate catalyst, the problem of low VOCs degradation efficiency at low temperature is solved, and the effect of efficient conversion of indoor pollutants in low temperature environments is achieved, and good stability and water resistance is achieved.

CN119406422AActive Publication Date: 2025-02-11CHINA STATE SHIPBUILDING CORP LTD RESEARCH INSTITUTE 719 +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411486640.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-11
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Under low temperature environment, existing catalysts are difficult to effectively degrade VOCs in confined spaces, especially triplet oxygen, which is difficult to dissociate into reactive oxygen species at low temperatures, limiting the progress of the reaction at low temperatures.

Method used

Using the preparation method of copper-manganese composite integral metal substrate catalyst, copper salt is added and hydrothermal reaction is carried out through the redox reaction of potassium permanganate and glucose to form a precursor material containing copper-manganese composite oxide, and then hydrophobic treatment is carried out. With air calcination, a copper-manganese composite metal substrate catalyst was prepared.

Benefits of technology

The catalyst can efficiently convert indoor pollutants such as formaldehyde, propane, toluene, trichloromethane and acetone at low temperatures, with a conversion rate of more than 90%, and has good stability and water resistance, avoiding the 20% caused by ozone spillage. Second pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406422A_ABST
    Figure CN119406422A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalyst material preparation, and particularly relates to a preparation method and application of a metal oxide monolithic catalyst, and the metal oxide monolithic catalyst provided by the invention is prepared by hydrothermally loading a copper-manganese composite oxide on a foam metal substrate, an oxide heterogeneous interface can be formed on the surface of the catalyst prepared by using the method, ozone is activated by using the electron delocalization effect of the oxide heterogeneous interface, high-active oxygen species are generated, activation energy required by reaction can be reduced without high temperature and high pressure, and meanwhile, the catalyst has good catalytic activity. The monolithic composite metal oxide catalyst is pretreated with hydrogen peroxide, a multi-stage structure can be formed on the surface of a substrate, and adsorption of organic pollutants can be greatly promoted through treatment of a surfactant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst material preparation, and in particular to a preparation method and application of a copper-manganese composite monolithic metal substrate catalyst. Background Art

[0002] In a closed environment, an integrated catalyst can be designed to integrate various technologies for application for different gaseous pollutants. Although the adsorption method can reduce the concentration of pollutants to the range specified by the state, it often takes a long time. After adsorption saturation, some pollutants may be released to cause secondary pollution to the environment. Most adsorbents on the market are disposable commodities, which are difficult to achieve long-term recycling. Chemical degradation is considered to be the most promising treatment technology due to its advantages such as high efficiency, environmental friendliness, and diverse applicable conditions. Chemical degradation is the complete and thorough conversion of VOCs into water and carbon dioxide with lower public health risks. It usually uses external energy such as heat, electricity, and light to cooperate with metal catalysts to degrade pollutants. Therefore, the energy consumption is usually high. In order to reduce the cost of external energy in the chemical degradation process, it is necessary to improve the performance of the catalyst to achieve the removal of pollutants in a low-temperature environment. However, there are many difficulties in the low-temperature degradation of VOCs in a closed environment, especially the triplet oxygen as an oxidant is difficult to dissociate into active oxygen species at low temperatures. This characteristic limits many reactions to be carried out at low temperatures.

[0003] Therefore, there is an urgent need for a catalyst that can deeply convert indoor pollutants in a low-temperature environment. Summary of the invention

[0004] In view of this, the present application proposes a method for preparing a copper-manganese composite monolithic metal substrate catalyst, comprising:

[0005] A. Dissolve potassium permanganate and glucose in water to carry out redox reaction to obtain a precursor solution;

[0006] B. adding copper salt to the precursor solution and stirring to obtain a precursor turbid solution;

[0007] C. placing the foamed metal in the precursor turbid liquid in step B for hydrothermal reaction to obtain a precursor material containing copper-manganese composite oxide;

[0008] D. soaking the precursor material in a surfactant for hydrophobic treatment;

[0009] E. The precursor material after the hydrophobic treatment in step D is subjected to air calcination treatment to obtain a copper-manganese composite monolithic metal substrate monolithic catalyst.

[0010] According to a specific embodiment of the present invention, in step A, the mass ratio of the potassium permanganate to the glucose is (0.5-1):1, and the pH of the precursor solution is 6-8.

[0011] According to a specific embodiment of the present invention, in step B, the copper salt includes copper nitrate and / or copper sulfate;

[0012] According to a specific embodiment of the present invention, the stirring time is 1-5 hours, the pH of the precursor turbid solution is 6-8, and the mass ratio of the potassium permanganate to the glucose and the copper salt is (0.5-1):1:(0.08-0.12).

[0013] According to a specific embodiment of the present invention, in step C, the foam metal is a foam metal pretreated with hydrogen oxide;

[0014] The foam metal is selected from foam nickel and / or foam copper;

[0015] The hydrothermal reaction is carried out in a hydrothermal kettle, the reaction temperature during the hydrothermal reaction is 120-170° C., and the reaction time is 8-12 hours;

[0016] After step C, the process further includes filtering, washing and drying the precursor material in sequence, wherein the drying temperature is 60-80° C. and the drying time is 10-12 hours.

[0017] According to a specific embodiment of the present invention, in step D, the surfactant includes at least one of hexadecyltrimethoxysilanetoluene and sodium hexadecylbenzenesulfonate.

[0018] According to a specific embodiment of the present invention, the surfactant is hexadecyltrimethoxysilanetoluene, the concentration of the hexadecyltrimethoxysilanetoluene is (45-60) g / L, and the duration of the hydrophobic treatment is 1-3 hours.

[0019] According to a specific embodiment of the present invention, in step E, the temperature during the air calcination treatment is 240-500° C., and the calcination time is 2-4 hours.

[0020] According to a specific embodiment of the present invention, the mass percentage of copper atoms in the copper salt to the copper-manganese composite oxide is 4-7%.

[0021] According to a specific embodiment of the present invention, the mass percentage of the copper-manganese composite oxide in the copper-manganese composite monolithic metal substrate monolithic catalyst is 4.5-6.5%.

[0022] The second aspect of the present invention provides a copper-manganese composite monolithic metal substrate catalyst, which is prepared by the method described in the first aspect. The copper-manganese composite monolithic metal substrate catalyst is used for ozone-synergistic catalytic oxidation reactions.

[0023] The third aspect of the present invention provides the role of the copper-manganese composite integral metal substrate catalyst described in the second aspect in the preparation of an air purifier.

[0024] The fourth aspect of the present invention provides an air purifier comprising the copper-manganese composite integral metal substrate catalyst described in the second aspect.

[0025] According to a specific embodiment of the present invention, the air purifier further includes: at least one of a filter, a fan, an adsorption plate, an ozone generator, an air duct, a catalytic chamber, a heat exchange plate, and an air outlet.

[0026] The fifth aspect of the present invention provides the use of the copper-manganese composite integral metal substrate catalyst described in the second aspect and the air purifier described in the fourth aspect in converting formaldehyde, propane, toluene, chloroform, acetone or ozone.

[0027] The present application designs an integral composite metal oxide catalyst, utilizes the electron delocalization effect of the oxide heterogeneous interface to activate ozone, produces highly active oxygen species, and converts gaseous pollutants present in a confined space at low temperature; at the same time, the multi-level pores and surface hydrophobic structure of the integral composite metal oxide catalyst can greatly promote the adsorption of organic pollutants and reduce the competitive adsorption of water vapor, and the strong ability to activate ozone can avoid secondary pollution caused by ozone overflow, thereby achieving efficient and low-cost conversion of indoor pollutants; considering the limited characteristics of the confined space, the integral catalyst has the characteristics of simple operation and easy replacement, and at the same time, a confined space integrated air purification device is assembled based on the composite metal oxide catalyst strategy; in summary, the present application prepares a low-cost integral catalytic material that can truly achieve confined space air purification, and assembles a confined space integrated air purification device that relies on the catalytic technology to operate.

[0028] When the prior art uses a catalyst to convert gaseous pollutants, the required activation energy is relatively high. Those skilled in the art usually reduce the activation energy required for the reaction by heating or pressurizing. The surface of the catalyst prepared by the method of the present application can form an oxide heterogeneous interface, and the electron delocalization of the oxide heterogeneous interface is used to activate ozone to produce highly active oxygen species, which can reduce the activation energy required for the reaction without the need for high temperature and high pressure. At the same time, the monolithic composite metal oxide catalyst is pretreated with hydrogen peroxide to form a multi-level structure on the substrate surface, and the treatment with a surfactant can greatly promote the adsorption of organic pollutants. Therefore, the catalyst obtained in the present application exhibits a high catalytic activity for gaseous pollutants in a relatively low temperature range. Compared with the prior art, the present application has the following beneficial effects:

[0029] (1) In the presence of 5% water vapor, the conversion rates of formaldehyde, propane, toluene, chloroform and acetone over the CMO-MO-NF catalyst at low temperature (60°C) were 100%, 96%, 98%, 90% and 97%, respectively, with a stability of more than 100 hours.

[0030] (2) The monolithic catalyst provided in this application has better oxidation effect than the traditional powder catalyst, and its preparation process is simple, easy to operate, low cost, high gas pollutant conversion rate, strong operation stability, and has obvious industrial application value;

[0031] (3) The composite metal oxide catalyst in the present application is used for ozone-coordinated catalytic oxidation reaction, has strong ozone decomposition ability, and its integral feature facilitates its application in confined spaces;

[0032] (4) The enclosed space air purification device in the present application is low-cost, easy to assemble, lightweight and environmentally friendly, small in size, and does not produce secondary pollution. It greatly meets the air purification needs of enclosed spaces and improves the comfort and health level of personnel. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 The durability test of the monolithic composite metal oxide catalyst (CMO-MO-NF) and the manganese-based catalyst (MO-N) for formaldehyde conversion at low temperature in Comparative Example 1 of the present application is as follows;

[0035] Figure 2 The durability test of the monolithic composite metal oxide catalyst (CMO-MO-NF) and the manganese-based catalyst (MO-N) for propane conversion at low temperature in Comparative Example 1 of the present application is as follows;

[0036] Figure 3 The durability test of the monolithic composite metal oxide catalyst (CMO-MO-NF) and the manganese-based catalyst (MO-N) for toluene conversion at low temperature in Comparative Example 1 of the present application is as follows;

[0037] Figure 4 The durability test of the monolithic composite metal oxide catalyst (CMO-MO-NF) and the manganese-based catalyst (MO-N) for chloroform conversion at low temperature in Comparative Example 1 of the present application is as follows;

[0038] Figure 5 The durability test of the monolithic composite metal oxide catalyst (CMO-MO-NF) and the manganese-based catalyst (MO-N) for acetone conversion at low temperature in Comparative Example 1 of the present application is as follows;

[0039] Figure 6 The durability test of the monolithic composite metal oxide catalyst (CMO-MO-NF) and the manganese-based catalyst (MO-N) for ozone conversion at low temperature in Comparative Example 1 of the present application is as follows;

[0040] Figure 7 The CMO-MO-NF prepared in Example 1 of the present application shows Cu 1.5 Mn 1.5 Characteristic diffraction of O4 (PDF#35-1172) and Mn2O3 (PDF#41-1442);

[0041] Figure 8 The ordinary transmission electron microscope spectra of the catalysts in Example 1 and Comparative Example 1 of the present application, wherein Figure a and Figure c respectively represent the electron microscope structure diagrams of the catalyst prepared in Comparative Example 1 at different magnifications; Figure b and Figure d respectively represent the electron microscope structure diagrams of the catalyst prepared in Example 1 at different magnifications;

[0042] Fig. 9 This is a diagram showing the exploration result of the Cu atomic mass ratio in Comparative Example 3 of the present application;

[0043] Fig.10 This is a cross-sectional schematic diagram of the assembled enclosed space air purifier in Example 4 of the present application. DETAILED DESCRIPTION

[0044] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0045] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0046] In this document, the terms "contain", "include" or "include" are open expressions, that is, they include the contents specified in the present application but do not exclude other contents.

[0047] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.

[0048] In order to make the technical means, creative features, objectives and effects achieved by this application easy to understand, this application provides drawings, which are part of the content disclosed in this application. They are mainly used to illustrate the embodiments and can be used in conjunction with the relevant descriptions in the specification to explain the operating principles of the embodiments. By referring to these contents, ordinary technicians in this field should be able to understand other possible implementation methods and the advantages of this application.

[0049] The following will be combined with the implementation methods of this application to clearly and completely describe the technical solutions in the implementation methods of this application. Obviously, the described implementation methods are only part of the implementation methods of this application, not all of the implementation methods. Based on the implementation methods in this application, all other implementation methods obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0050] Example 1 Preparation of Monolithic Catalyst

[0051] 1. Pretreatment of foam metal:

[0052] The cut foam metal sheets are placed in a 30% hydrogen peroxide aqueous solution for treatment for 1-2 hours.

[0053] 2. Preparation of precursor:

[0054] (1) Dissolve 0.79 g potassium permanganate and 1.00 g glucose in 50 mL deionized water and stir for 1-2 h;

[0055] (2) adding 0.1 g of copper nitrate solid to the solution obtained in step (1), and stirring for 3-4 hours to obtain a precursor turbid solution;

[0056] (3) placing the foamed metal support obtained by the pretreatment in the solution obtained in (2) and transferring it to an oven in a hydrothermal kettle, maintaining it at 150° C. for 10 hours, filtering, washing, and drying;

[0057] (4) Immerse 0.4 g of the precursor material obtained in step (3) in a 50 g / L hexadecyltrimethoxysilane toluene solution and stir for 1-2 hours, centrifuge, wash, and dry.

[0058] 3. Calcination:

[0059] The prepared precursor was calcined at 250 °C in air for 3 h to obtain a monolithic catalyst named CMO-MO-NF.

[0060] Comparative Example 1

[0061] The difference from Example 1 is that, during the precursor preparation process, the Mn2O3 solution obtained in step (1) is directly subjected to a hydrothermal reaction on a foam metal carrier, i.e., pure Mn2O3 that has not been modified by copper doping is loaded on the foam metal for preparation (step 2 is omitted), and the resulting integral catalyst is named MO-NF.

[0062] Determination of the conversion rate of pollutants in Example 1 and Comparative Example 1 under low temperature conditions:

[0063] The filling volume of CMO-MO-NF and MO-NF is 10*10cm -3 , initial gas concentration: formaldehyde is 100ppb, ozone is 10ppm, oxygen is 20vol%, water content is 5%, nitrogen is the carrier gas, and the volume space velocity is 10,000h -1 ; Propane is 120ppb, ozone is 10ppm, oxygen is 20vol%, water content is 5%, nitrogen is the carrier gas, and the volume space velocity is 10,000h -1 ; Toluene is 200ppb, ozone is 10ppm, oxygen is 20vol%, water content is 5%, nitrogen is the carrier gas, and the volume space velocity is 10,000h -1 , chloroform is 80ppb, ozone is 10ppm, oxygen is 20vol%, water content is 5%, nitrogen is the carrier gas, and the volume space velocity is 10,000h -1 , acetone is 80ppb, ozone is 10ppm, oxygen is 20vol%, water content is 5%, nitrogen is the carrier gas, and the volume space velocity is 10,000h -1 The test temperature for each pollutant is 60℃, and the results are as follows: Figure 1-6 shown.

[0064] from Figure 1 It can be seen that the catalysts prepared in Example 1 can achieve a 100% conversion rate of formaldehyde at 60°C and maintain it for 10 hours;

[0065] from Figure 2 It can be seen that the catalysts prepared in Example 1 can achieve a propane conversion rate of 96% at 60°C and maintain it for 10 hours;

[0066] from Figure 3 It can be seen that the catalysts prepared in Example 1 can achieve a toluene conversion rate of 98% at 60°C and maintain it for 10 hours;

[0067] from Figure 4 It can be seen that the catalysts prepared in Example 1 can achieve a 90% conversion rate of chloroform at 60°C and maintain it for 10 hours;

[0068] from Figure 5 It can be seen that the catalysts prepared in Example 1 can achieve a conversion rate of 97% of acetone at 60°C and maintain it for 10 hours;

[0069] from Figure 6 It can be seen that the catalysts prepared in Example 1 can achieve complete conversion of ozone at 60° C. and maintain it for 10 hours.

[0070] The inventors conducted XRD tests on MO-NF and CMO-MO-NF, and the results were as follows: Figure 7 As shown, the CMO-MO-NF prepared in Example 1 shows Cu 1.5 Mn 1.5 The characteristic diffraction patterns of O4 (PDF#35-1172) and Mn2O3 (PDF#41-1442) indicate that it is composed of two metal oxides.

[0071] The inventors conducted microscopic observations on MO-NF and CMO-MO-NF, and the results were as follows: Figure 8 As shown, Figure 8 The left image shows pure Mn2O3 without copper doping modification, showing a spindle-shaped structure (Figure a). After zooming in, it can be seen that there are obvious boundaries between particles (Figure c); Figure 8 The right side of the figure shows the catalyst prepared in Example 1, which is composed of spindle-shaped Mn2O3 and nanosheet-shaped Cu 1.5 Mn 1.5 The microscopic morphology of the O4 composition (Figure b) shows after magnification that an obvious heterogeneous interface can be formed between the two phases (Figure d).

[0072] Comparative Example 2

[0073] The difference from Example 1 is that in the precursor preparation process, glucose is not added in step (1), potassium permanganate is directly dissolved in deionized water, and the obtained potassium permanganate aqueous solution is used for the subsequent reaction. The final monolithic catalyst is named CMO-NF.

[0074] The conversion rate of pollutants of the finally obtained monolithic catalyst CMO-NF under low temperature conditions was measured, and the measuring method was the same as described in Comparative Example 1.

[0075] The results show that the catalysts prepared in Comparative Example 2 can achieve a formaldehyde conversion rate of 80% at 60°C and maintain it for 10 hours;

[0076] The catalysts prepared in Comparative Example 2 were able to achieve a propane conversion rate of 70% at 60°C and maintain it for 10 hours;

[0077] The catalysts prepared in Comparative Example 2 were able to achieve a toluene conversion rate of 67% at 60°C and maintain it for 10 hours;

[0078] The catalysts prepared in Comparative Example 2 were able to achieve a 60% conversion rate of chloroform at 60°C and maintain this rate for 10 hours;

[0079] The catalysts prepared in Comparative Example 2 were able to achieve a conversion rate of 68% of acetone at 60°C and maintain it for 10 hours;

[0080] The catalysts prepared in Comparative Example 2 were able to achieve an ozone conversion rate of 73% at 60° C. and maintain it for 10 hours.

[0081] The inventors speculate that if glucose is not added in step (1), high-valent manganese cannot be generated, and further, an oxide heterogeneous interface cannot be formed, which affects the conversion rate of pollutants.

[0082] Comparative Example 3

[0083] The difference from Example 1 is that during the precursor preparation process, the content of copper nitrate added in step (2) is different.

[0084] The inventors set up 5 experimental groups according to different contents of copper nitrate, and measured the conversion rates of formaldehyde, propane, toluene, chloroform, acetone and ozone in different experimental groups at 60°C. The results are shown in Table 1.

[0085] Table 1

[0086]

[0087] The inventors used the ICO-OES method to explore the atomic mass ratio of Cu, and the results are as follows Fig. 9 As shown, it is shown that the content of Cu atoms in the copper-manganese composite oxide is between 4-7% to form a two-phase heterogeneous interface.

[0088] Example 2 Assembly of air purification device in enclosed space

[0089] Considering the air flow path, material strength, durability, sealing and safety, the shell was designed using Solidworks software, and the plastic and metal parts of the shell were made using injection molding and die casting processes. In order to ensure the lightness of the shell, glass fiber reinforced plastic was used as the raw material for the plastic part.

[0090] During the assembly process, a small ozone generator and a fan are installed, and a catalytic chamber is assembled, and the monolithic catalyst prepared in Example 3 is filled in the chamber to achieve an effective air purification effect. At the same time, circuit boards, sensors, controllers, and power modules are assembled to ensure the normal operation and intelligent control function of the air purification device.

[0091] Finally, the internal components are assembled with the outer shell to complete the production of the confined space air purification device. This design and manufacturing process aims to provide an efficient and reliable confined space air purification device that can meet performance requirements while ensuring product safety and reliability. Fig.10 It is a cross-sectional schematic diagram of a closed space air purification device, wherein 1 is a primary filter, 2 is a fan, 3 is an adsorption plate, 4 is a strong adsorption plate, 5 is an ozone generator, 6 is an air duct, 7 is a catalytic compartment, 8 is an integral catalyst, 9 is a heat exchange plate, and 10 is an air outlet. The closed space air purification device improved by the present invention has low cost, easy assembly, light weight and environmental protection, small size, and does not produce secondary pollution, which greatly meets the needs of closed space air purification and improves the comfort and health level of personnel.

[0092] In summary, the present invention provides an integral catalyst material for efficient degradation of low-concentration pollutants in a confined space, and an integrated air purification device. The catalyst is prepared by hydrothermally loading a copper-manganese composite oxide on a foam metal substrate. The manganese-based catalyst itself has good performance on indoor volatile organic pollutants. After copper doping by hydrothermal method, an oxide-oxide heterogeneous interface is formed. Due to the delocalization of interface electrons, it has the ability to activate ozone at low temperature, and can achieve catalyst synergistic ozone activation. The active oxygen species produced by ozone can show good pollutant oxidation performance at low temperature. The integral catalyst can completely mineralize more than 90% of gaseous pollutants at low temperature, showing good catalytic activity; this excellent oxidation performance also comes from the material's good ability to decompose ozone at low temperature, and 100% activation of ozone can be achieved at low temperature. The catalytic combustion performance of the catalyst provided by the present invention is better than that of the traditional powder catalyst, and its preparation process is simple, easy to operate, low cost, high gaseous pollutant conversion rate, and strong anti-poison and water resistance. The integrated air purification device provided by the present invention is easy to install and has low cost. Tests have found that the total pollutant purification rate of air in a closed space can reach 90% in one pass. It has good application prospects and greatly improves the air environment in the closed space.

[0093] The above description is only a preferred implementation mode of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a copper-manganese composite monolithic metal substrate catalyst, characterized in that: include: A. Dissolve potassium permanganate and glucose in water to carry out redox reaction to obtain a precursor solution; B. adding copper salt to the precursor solution and stirring to obtain a precursor turbid solution; C. placing the foamed metal in the precursor turbid liquid in step B for hydrothermal reaction to obtain a precursor material containing copper-manganese composite oxide; D. soaking the precursor material in a surfactant for hydrophobic treatment; E. The precursor material after the hydrophobic treatment in step D is subjected to air calcination treatment to obtain a copper-manganese composite monolithic metal substrate monolithic catalyst.

2. The method according to claim 1, characterized in that In step A, the mass ratio of the potassium permanganate to the glucose is (0.5-1):1, and the pH of the precursor solution is 6-8; In step B, the copper salt includes copper nitrate and / or copper sulfate; The stirring time is 1-5 hours, the pH of the precursor turbid solution is 6-8, and the mass ratio of the potassium permanganate to the glucose and the copper salt is (0.5-1):1:(0.08-0.12).

3. The method according to claim 1, characterized in that In step C, the foam metal is a foam metal pretreated with hydrogen peroxide; The foam metal is selected from foam nickel and / or foam copper; The hydrothermal reaction is carried out in a hydrothermal kettle, the reaction temperature during the hydrothermal reaction is 120-170° C., and the reaction time is 8-12 hours; After step C, the process further includes filtering, washing and drying the precursor material in sequence, wherein the drying temperature is 60-80° C. and the drying time is 10-12 hours.

4. The method according to claim 1, characterized in that In step D, the surfactant includes at least one of hexadecyltrimethoxysilanetoluene and sodium hexadecylbenzenesulfonate; The surfactant is hexadecyltrimethoxysilane toluene, the concentration of the hexadecyltrimethoxysilane toluene is (45-60) g / L, and the duration of the hydrophobic treatment is 1-3 hours.

5. The method according to claim 1 or 2, characterized in that: In step E, the temperature during the air calcination treatment is 240-500° C., and the calcination time is 2-4 hours; The mass percentage of copper atoms in the copper salt to the copper-manganese composite oxide is 4-7%; The mass percentage of the copper-manganese composite oxide to the copper-manganese composite monolithic metal substrate monolithic catalyst is 4.5-6.5%.

6. A copper-manganese composite monolithic metal substrate catalyst, characterized in that: The copper-manganese composite monolithic metal substrate catalyst is prepared by the method described in any one of claims 1 to 5 and is used for ozone-synergistic catalytic oxidation reactions.

7. The role of the copper-manganese composite monolithic metal substrate catalyst as claimed in claim 6 in the preparation of an air purifier.

8. An air purifier, characterized in that: Contains the copper-manganese composite monolithic metal substrate catalyst as described in claim 6.

9. The air purifier according to claim 8, characterized in that: Also includes: Filter, fan, adsorption plate, ozone generator, air duct, catalytic chamber, heat exchange plate, and air outlet.

10. Use of the copper-manganese composite integral metal substrate catalyst according to claim 6 and the air purifier according to claim 8 or 9 in converting formaldehyde, propane, toluene, chloroform, acetone or ozone.

Citation Information

Patent Citations

  • Fresh air and indoor air purification integrated device and purification method

    CN106642487A

  • Preparation method of catalytic material for removing ozone at room temperature

    CN109433272A

  • Preparation method and application of rod-like ozone catalyst Cu-OMS-2

    CN110314689A

  • High-activity foamy copper monolithic catalyst and synthesis method and application of high-activity foamy copper monolithic catalyst

    CN110586125A

  • Spinel type copper-manganese sterilizing and aldehyde-removing catalytic material as well as preparation method and application thereof

    CN113198486A